(untitled) (Research, Society and Development, 2022)
Industry 4.0 is based on digital technological advances that demand educational processes that develop people to act in line with this scenario. Based on the ecological and systemic view, mainly on the concepts of bidirectionality and self-eco-organization, the aim of this text is to reflect on the effect of the connection between education 4.0 and industry 4.0 in Brazil in the constitution of subjectivity. Narrative review was applied in the fields of History and Philosophy of Education, Brazilian Industrialization and Educational and Organizational Psychology, to support a Brazilian socio-historical reading of the four industrial revolutions and their parallel with education, the influence on the Brazilian subjective position is inferred. Ethically positioned in terms of human and professional training, it is argued that technological advances should be at the service of human beings and not the other way around. In this sense, we conclude that dialogic and emancipatory education, aware of its subjective influence, has an important role in social justice. The appreciation of subjectivity supported by the construction of autonomy and thought authorship can serve as key elements to educational success in connection with Industry 4.0.